2022
DOI: 10.5937/jomb0-34718
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of three thyrotropin receptor antibody assays in thyroid-associated orbitopathy

Abstract: Background: Thyrotropin receptor autoantibodies (TSH-R-Ab) are indispensable biomarkers in the laboratory assessment of thyroid-associated orbitopathy (TAO). Clinical sensitivity of three different assays for TSH-R-Ab determination was evaluated in patients with TAO. Methods: 87 consecutive TAO patients were enrolled and their serum samples analyzed in parallel with three assays. An ECLIA competitive binding and a chemiluminescent bridge immunoassay were used to measure total and binding TSH-R-Ab concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The role of the TSH-Receptor antibodies, is unclear although they likely play a crucial role in the pathogenesis of TED. A variety of antibodies exist including stimulating, blocking and neutralising and how these antibodies interact with the TSH-Receptor at different type points on Rundle’s curve is not fully understood [ 119 , 120 ]. The different forms of antibodies, may predominate and impact certain ethnic populations to various degrees [ 121 , 122 ].…”
Section: Targeting Orbital Fibroblast Receptorsmentioning
confidence: 99%
“…The role of the TSH-Receptor antibodies, is unclear although they likely play a crucial role in the pathogenesis of TED. A variety of antibodies exist including stimulating, blocking and neutralising and how these antibodies interact with the TSH-Receptor at different type points on Rundle’s curve is not fully understood [ 119 , 120 ]. The different forms of antibodies, may predominate and impact certain ethnic populations to various degrees [ 121 , 122 ].…”
Section: Targeting Orbital Fibroblast Receptorsmentioning
confidence: 99%
“…For ESR estimation, the Westergren's method was used [13] . Measuring TSH was performed using Cobas ECLIAs (Roche Diagnostics GmbH, Mannheim, Germany) [14] .…”
Section: Laboratory Examinationmentioning
confidence: 99%
“…The superior sensitivity of TSI over TBII has later been confirmed in subcategories of TED, including euthyroid patients and mild cases of TED. [27][28][29] There is evidence supporting a correlation between TSI levels and CAS, and some studies indicated that TSI levels also correlate with the severity of TED. [30][31][32] Furthermore, TSI has been evaluated for predicting active TED with a sensitivity of 77.4%, specificity of 81.3%, and area under the curve (AUC) of 84.7%.…”
Section: Validated Blood Biomarkers In Current Clinical Usementioning
confidence: 99%